Spring Garden Packet Well Received - Bud Gavitt (Journal of Applied Communications, 1983)
In early March of 1982 we conducted a mail survey of newspaper editors and others in Connecticut to determine whether they would like to receive a spring packet of lawn and garden feature stories and a few pages of garden fillers.